Radiation Shielding Tests of Crosslinked Polystyrene-b-Polyethyleneglycol Block Copolymers Blended with Nanostructured Selenium Dioxide and Boron Nitride Particles - Zehra Merve Cinan; Burcu Erol; Taylan Baskan; Saliha Mutlu; Bülend Ortaç; Sevil Savaskan Yilmaz; Ahmet Hakan Yilmaz (Nanomaterials, 2022)
In this work, gamma-ray shielding features of crosslinked polystyrene-b-polyethyleneglycol block copolymers (PS-b-PEG) blended with nanostructured selenium dioxide (SeO2) and boron nitride (BN) particles were studied. This research details several radiation shielding factors i.e., mass attenuation coefficient (<semantics>μm</semantics>), linear attenuation coefficient (<semantics>μL</semantics>), radiation protection efficiency (RPE), half-value layer (HVL), tenth-value layer (TVL), and mean free path (MFP). The irradiation properties of our nanocomposites were investigated with rays from the 152Eu source (in the energy intervals from 121.780 keV to 1408.010 keV) in a high-purity germanium (HPGe) detector system, and analyzed with GammaVision software. Moreover, all radiation shielding factors were determined by theoretical calculus and compared with the experimental results. In addition, the morphological and thermal characterization of all nanocomposites was surveyed with various techniques i.e., nuclear magnetic resonance (NMR), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and transmission electron microscopy (TEM). Acceptable compatibility was revealed and observed in all nanocomposites between the experimental and theoretical results. The PS-b-PEG copolymer and nanostructured SeO2 and BN particles exerted a significant effect in enhancing the resistance of the nanocomposites, and the samples with high additive rates exhibited better resistance than the other nanocomposites. From the achieved outcomes, it can be deduced that our polymer-based nanocomposites can be utilized as a good choice in the gamma-irradiation-shielding discipline.